Vitamin D and periodontitis; is there an association between vitamin D deficiency and periodontitis severity? A cross-sectional study - Lindholm, Fanny (UiT Norges arktiske universitet, 2022)
Background: Periodontitis is an oral disease which is highly prevalent in the adult population worldwide. Periodontitis is characterized by an excessive inflammatory reaction which leads to the destruction of supportive periodontal tissues and potentially tooth loss in the more severe stages of disease. Known risk factors for periodontitis include conditions and lifestyle factors which increase the person’s overall inflammatory risk. Vitamin D has recently been found to play an important role in the immune system and in regulating inflammatory processes. Over the recent decades, there has been an increase in studies investigating the potential influence of vitamin D status on inflammatory diseases and conditions. However, there is still little research to be found on the relationship between vitamin D and periodontitis. The aim of this study was to examine the associations between levels of serum 25(OH)D and periodontitis stage and periodontal pocket depth in Norwegian adults. Methods: The study design was cross-sectional. The data used was obtained from the population-based Tromsø 7 study conducted in 2015 – 2016. From the original Tromsø 7 study sample, only those who had both a valid periodontal diagnosis and data on serum 25(OH)D levels were included in the present study, giving a total study sample of 3 693 participants. Using descriptive statistics and bivariate logistic regression analysis, associations were tested. Periodontitis stage and number of periodontal pockets of ≥ 5 mm were used as dependent variables for their respective separate analyses, and serum 25(OH)D was used as the independent variable for both. An additional analysis of vitamin D and periodontitis stage was performed in which participants were split into two groups according to whether blood samples had been collected between March and September or between October and February. All results were adjusted for selected covariates included in the analyses. Results: Most participants had periodontitis (89.2%) and 19.8% were classified as ...